Bio-inspired antibacterial cellulose paper–poly(amidoxime) composite hydrogel for highly efficient uranium(vi) capture from seawater. Issue 28 (20th March 2020) - Gao, Jinxiang; Yuan, Yihui; Yu, Qiuhan; Yan, Bingjie; Qian, Yongxin; Wen, Jun; Ma, Chunxin; Jiang, Shaohua; Wang, Xiaolin; Wang, Ning
Abstract : We have developed a new bio-inspired tough antibacterial cellulose paper–poly(amidoxime) composite hydrogel membrane with ultra-efficient uranium adsorption capacity and broad-spectrum antibacterial performance. Abstract : A bio-inspired cellulose paper–poly(amidoxime) composite hydrogel is explored via UV-polymerization. This hydrogel has a highly efficient uranium capture capacity of up to 6.21 mg g −1 for WU /Wdry gel and 12.9 mg g −1 for WU /Wpoly(amidoxime) in seawater for 6 weeks, due to its enhanced hydrophilicity, good hydraulic/ionic conductivity and broad-spectrum antibacterial performance.